AN ULTRASTRUCTURAL-STUDY ON THE ENDOCRINE PANCREAS OF CAIMAN-LATIROSTRIS, WITH SPECIAL REFERENCE TO PANCREATIC MOTILIN CELLS - Ono, K.; Yamada, J.; DPAI, V; Kitamura, N.; Gregorio, E. A.; Yamashita, T.; Campos, VJM (Japan Soc Histol Documentation Niigata Univ Medical School, 1991)
Pancreatic endocrine cells of Caiman latirostris were investigated by electron microscopy using conventional and immunocytochemical methods. Ultrastructurally, four types of endocrine cells were classified according to the morphology of their secretory granules. Three types of endocrine cells were identified as either glucagon, insulin or somatostatin cells by the presence of such characteristic granules well established in mammals. The remaining endocrine cell type could not be classified by its ultrastructural features alone.Immunocytochemical observations confirmed the ultrastructural classification of glucagon, insulin and somatostatin cells. In addition, endocrine cells immunoreactive for either pancreatic polypeptide (PP) or motilin were identified. Morphometric analysis of PP- and motilin-immunoreactive granules demonstrated that they were the most polymorphous and smallest granules among the pancreatic endocrine cell granules. Although both PP and motilin granules closely resemble each other, motilin granules were smaller in size and more spherical in shape than PP granules.